Prevalência de sintomas de incontinência urinária em atletas do esporte paralímpico - BARBOSA, Pedro Renan Nascimento (Universidade Federal do Pará, 2025)
Background: Paralympic sport is sport adapted to include people with disabilities. In sports in general, due to the characteristics of the level of performance, health problems are prevalent and urinary incontinence can be one of them. However, there is little epidemiological data in the literature on such alterations in para-athletes. Aim: To verify the prevalence of urinary incontinence symptoms in paralympic athletes. Material and Methods: This was an observational, cross-sectional, quantitative and descriptive epidemiological study of paralympic athletes from all disciplines. Data was collected using an electronic form that included an ICF, sociodemographic data, the International Consultation on Incontinence Questionnaire (ICIQ-UI Short Form) and the International Consultation on Incontinence Questionnaire Overactive Bladder (ICIQ-OAB). Results: The prevalence of urinary incontinence in the sample (n=95) was 47.36%, with moderate severity (40.00%) and an impact on quality of life averaging 7±3